2014
DOI: 10.1080/02791072.2014.960110
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of the Efficacy of an Interoceptive Exposure-Based CBT for Treatment-Refractory Outpatients with Opioid Dependence

Abstract: Many patients diagnosed with opioid dependence do not adequately respond to pharmacologic, psychosocial, or combination treatment, highlighting the importance of novel treatment strategies for this population. The current study examined the efficacy of a novel behavioral treatment focusing on internal cues for drug use (Cognitive Behavioral Therapy for Interoceptive Cues; CBT-IC) relative to an active comparison condition, Individual Drug Counseling (IDC), when added to methadone maintenance treatment (MMT) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…This study found no difference in any measure between the three treatment arms. This mirrors recent findings in prescription opioid dependence where the addition of counselling to OST made no difference to drug related outcomes [ 55 ], and in treatment-refractory opioid dependent individuals where there was no evidence for the superiority of a cognitive behavioural intervention over an active comparison condition [ 56 ]. Another study cited loss of hope as a reason for non-attendance at counselling sessions [ 57 ].…”
Section: Discussionsupporting
confidence: 78%
“…This study found no difference in any measure between the three treatment arms. This mirrors recent findings in prescription opioid dependence where the addition of counselling to OST made no difference to drug related outcomes [ 55 ], and in treatment-refractory opioid dependent individuals where there was no evidence for the superiority of a cognitive behavioural intervention over an active comparison condition [ 56 ]. Another study cited loss of hope as a reason for non-attendance at counselling sessions [ 57 ].…”
Section: Discussionsupporting
confidence: 78%
“…In addition, our review found two studies using interoception in substance use disorders with differing results; the mindfulness based intervention showed some statistically significant results, while CBT for interoceptive cues did not. 37,73 Paulus and colleagues review treatment for interoceptive dysfunction in addiction and highlight potential approaches to modulate interoceptive function and insular activation patterns, including mindfulness-based approaches and physical exercise. 81 Paulus and colleagues also discuss the role of increasing the frontal control network and reducing urges through cognitive training.…”
Section: Discussionmentioning
confidence: 99%
“…A subset of studies focused on sub-populations of individuals receiving OAT that (a) had an additional substance use condition [n = 6, 8.3%; these included cocaine use (n = 4, 5.6%) [67,71,76,80], moderate to heavy alcohol use (n = 1, 1.4%) [39], or sedative/hypnotic dependence (n = 1, 1.4%) [85], (b) had a psychiatric disorder or prominent symptoms associated with a psychiatric disorder [n = 5, 6.9%, including a personality disorder (n = 2, 2.8%) [68,79], personality or psychiatric disorder (n = 1, 1.4%) [95], depression (n = 1, 1.4%) [45], or mid-to high level psychiatric symptoms (n = 1, 1.4%) [93], (c) were pregnant women (n = 3, 4.2%) [55,91,98], (d) were veterans (n = 2, 2.8%) [92,94], (e) were positive for HIV (n = 2, 2.8%) [54,70], (f) had chronic low back pain (n = 1, 1.4%) [103] or (g) were described as being in poor mental or physical health based on a predetermined cutoff on the Opiate Treatment Index Health Symptoms Scale of the Global Severity Index of the Symptom Check-list (n = 1, 1.4%) [62]. One study only recruited individuals that had "failed to respond to the standard course of treatment" [46]. [40,42,43,45,68,71,73,76,77,88,92,95,97], alcohol use [42, 43, 58, 80-83, 88, 92, 95, 104], adherence to OAT [42,43,49,…”
Section: Study Populationsmentioning
confidence: 99%
“…One study only recruited individuals that had "failed to respond to the standard course of treatment" [46]. [40,42,43,45,68,71,73,76,77,88,92,95,97], alcohol use [42, 43, 58, 80-83, 88, 92, 95, 104], adherence to OAT [42,43,49,53,54,61,72,86,102,110], HIV/HCV risk behavior [54,57,60,61,67,88,89,91,105], withdrawal symptoms [40,49,65,73,86,87,96], adverse events [49,58,75,102], measure of craving [49,83], relapse prevention [41,106], drop-outs from...…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation